Stages of the formation of IT speciality students’ pragma-professional communicative competence in foreign language education - Zhaiykbay, K.T.; Diankova, G.; Zhussipbek, T.Z. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2023)
The article deals with the stages of the formation of IT specialty students’ pragma-professional communicative competence in foreign language education. The pragma-professional communicative competence has four subcompetences such as pragma-communicative sub-competence, functional-projective sub-competence, discursive- industrial sub-competence, pragma-creative sub-competence. Researcher conducted an experiment with 208 IT specialty students and 10 students were selected to focus group interview. The experiment was aimed to identify the effectiveness of the awareness of stages for the formation of named competence. Before the experiment, the term “pragma-professional communicative competence” and stages for the formation were explained in detail. Pre-test and post-test questions were consisted of 40 various questions. The results of the pre and post tests were analyzed, and the experimental group had shown a significant change from 73 points to 90 points. Focus group interview was aimed to identify students’ perceptions of the formation of pragma-professional communicative competence and its stages. As this study was interested in understanding the perceptions of students about a focused topic, it was felt that a focus group approach was most appropriate. The reason for utilizing focus groups, rather than individual interviews, was that they were pragmatic and time efficient as they are perceived as a tool that can provide relevant data. Focus group interview result shows that students perceive stages for the formation of PPCC as helpful and comfortable to apply in foreign language education.
IT мамандығы студенттерінің шет тілін оқытудағы прагма-кәсіби коммуникативтік құзыреттілігін қалыптастыру кезеңдері
Этапы формирования прагма-профессиональной коммуникативной компетенции студентов IТ-специальностей в иноязычном образовании
Keywords: foreign language education; stages; pragma-professional communicative competence; IT specialty; perception; formation; focus group; experiment